1999
DOI: 10.1046/j.1365-2044.1999.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior mediastinal masses: an anaesthetic challenge

Abstract: SummaryA patient with a large anterior mediastinal mass with minimal respiratory symptoms presented for a diagnostic biopsy of the mass. A pre-operative thoracic computed tomographic scan demonstrated narrowing of the distal trachea, and right and left main stem bronchi. An awake intubation was done. Thiopentone and muscle relaxant were given and surgery commenced. High airway pressure developed and ventilation became difficult, although oxygenation remained satisfactory throughout. Anaesthetic implications ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 19 publications
0
86
0
6
Order By: Relevance
“…This procedure was previously reported as part of the anesthetic management of an anterior mediastinal mass, where the possibility of precipitating airway obstruction existed. 9 In summary, we have reported a case of intraoperative lower respiratory tract obstruction in a patient with primary laryngo-tracheo-bronchial amyloidosis. This is a recurrent disease and despite repeated treatments with bronchoscopic procedures, airway compromise can be a persistent problem.…”
Section: éLéments Cliniques : Un Homme De 53 Ans a éTé Dirigé Vers Nomentioning
confidence: 84%
“…This procedure was previously reported as part of the anesthetic management of an anterior mediastinal mass, where the possibility of precipitating airway obstruction existed. 9 In summary, we have reported a case of intraoperative lower respiratory tract obstruction in a patient with primary laryngo-tracheo-bronchial amyloidosis. This is a recurrent disease and despite repeated treatments with bronchoscopic procedures, airway compromise can be a persistent problem.…”
Section: éLéments Cliniques : Un Homme De 53 Ans a éTé Dirigé Vers Nomentioning
confidence: 84%
“…How to establish safe and efficient gas exchange is the key to the successful management of the patients with critical tracheal stenosis and to survival. It is reported that cardiopulmonary bypass is widely used in non-cardiac operations (Belmont et al, 1998;Chuqhtai et al, 2002;Goh et al, 1999). It could allow gas exchange and good surgical access for the tracheal operations and avoid aggravating hypoxia and carbon dioxide accumulation which may result in cardiac arrest during normal anesthesia and tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The anaesthetic literature continues to report serious or fatal complications associated with unexpected, and sometimes apparently asymptomatic, compression of the trachea or main bronchus. The problems are well described in a case report in this issue of the journal [10]. Sudden respiratory obstruction can happen at any stage of the anaesthetic.…”
Section: Lower Tracheal and Bronchial Obstructionmentioning
confidence: 91%